The Decay Resistance and Hyphae Penetration of Bamboo Gigantochloa scortechinii Decayed by White and Brown Rot Fungi - Norul Hisham Hamid; Othman Sulaiman; Azmy Mohammad; Norasikin Ahmad Ludin (International Journal of Forestry Research)
The decay resistance and hyphae penetration of bamboo Gigantochloa scortechinii decayed by white and brown rot fungi were investigated using scanning electron microscope (SEM). The bamboo grown in natural stand from three different age classes of 0.5, 3.5, and 6.5 years was harvested, oven dried, sterilised, and exposed to agar media containing 4% malt extract and 2% agar technical (no. 3) under laboratory condition for 8 weeks. The deterioration was expressed as percentage of weight loss, and the decay resistance classes were measured according to ASTM D 2017-81 (1986). This study found that the percentage weight loss was greatly reduced with the bamboo ageing. Regardless of age, the G. scortechinii was classified as highly resistant to decay by white and brown rot fungi. The scanning electron microscope (SEM) observation showed that the fungi hyphae mostly penetrated into the vessel and proceeded to the pit and parenchyma cells.